Fixed Point Theorems via Auxiliary Functions - Erdal Karapınar; Peyman Salimi (Journal of Applied Mathematics)
We prove new fixed point theorems in the framework of partially ordered metric spaces. The main result is an extension and a generalization of many existing results in the literature. An example is also considered to illustrate the main result.